Proof Without Words : The Sum of the First n Odd Integers is a Perfect Square - Sinha, Ritam (Ohio Journal of School Mathematics, 2022)
In this proof without words, we prove wordlessly the identity 1+3+5+...+(2n-1)=n^2.